Transcriptomic and Metabolomic Differences Between Two Saposhnikovia divaricata (Turcz.) Schischk Phenotypes With Single- and Double-Headed Roots - Zhang, Tao; Chen, Yuqiu; Zhang, Qinghe; Yu, Peng; Li, Qiong; Qi, Weichen; Chen, Changbao (Frontiers in Bioengineering and Biotechnology, 2021)
Saposhnikovia divaricata is derived from the dried roots of Saposhnikovia divaricata (Turcz.) Schischk and used as a Chinese herbal medicine material for treating respiratory, immune, and nervous system diseases. The continuously increasing market demand for traditional Chinese medicine requires the commercial cultivation of Saposhnikovia divaricata using standardized methods and high yielding genotypes, such as double-headed root plants, for achieving consistent quality and reliable supply. In this study, we aimed to identify quantitative differences in chromone, a precursor of flavonoid biosynthesis, between plants with single-headed and double-headed roots using high-performance liquid chromatography and further explore the two phenotypes at the transcriptomic and metabolomic levels. Our results showed that chromone content was significantly higher in plants with double-headed roots than those with single-headed roots. Transcriptomic analysis revealed 6 significant differentially expressed genes between the two phenotypes, including 5 key genes in the flavonoid synthesis pathway (4-coumarate CoA ligase, chalcone synthase 1, vinorine synthase, chalcone-flavonone isomerase 1, and flavanone 3 beta-hydroxylase) and 1 key gene in the abscisic acid biosynthetic pathway (zeaxanthin epoxidase). Besides, metabolomic analysis showed that the 126 differentially expressed metabolites were mainly enriched in the biosynthesis of secondary metabolites and phytohormones. Overall, our study suggested that plants with double-headed roots had higher medicinal value than those with single-headed roots, probably due to differences in various biosynthetic pathways. These data might help select genotypes with superior yield potential and therapeutic properties.